A review on solar dryers integrated with thermal energy storage units for drying agricultural and food products. (15th November 2021) - Srinivasan, G.; Rabha, D.K.; Muthukumar, P.
Highlights: A review on solar dryers integrated with thermal storage unit is presented. Covers direct, indirect and mixed mode solar dryers in active and passive mode. Summaries works reported on sensible and latent heat storage materials. Provides a summary on future direction of research on solar dryers with TES. Abstract: Solar dryers utilise solar radiation for producing hot air to dry various food and agricultural products. The limitation of solar dryers is their inability to achieve continuous drying during off sunshine hours. Thus, solar dryers are integrated with thermal energy storage units to achieve continuous drying operation. The thermal energy storage unit employed in solar dryer consists of either sensible, latent heat storage systems or the combination of these two. The article provides an extensive review on the various sensible and latent storage units and materials used in different solar dryers viz., direct type, indirect and mixed-mode type dryers operated in both natural and forced convection. A detailed discussion on different dryer types, product dried, operating parameters, sensible and latent heat storage materials used, and their outcomes are reported and tabulated. Further, the article also provides a detailed summary on the implementation of thermal storage units in solar dryers. The future challenges and recommendations on the selection, implementation and testing of the thermal storage unit for different solar dryers are also reported.